The Effect of Emotional Intelligence and Compensation on Employee Performance Mediated by Job Satisfaction - Aprillova, Carmelita Virry Clarissa; Liana, Lie (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to analyze the influence of emotional intelligence and compensation on employee performance mediated by job satisfaction. This study uses a quantitative approach with a population of 80 employees of PT. Hanazono Engineering Indonesia. Data were processed using SPSS software version 26. Data analysis techniques include respondent descriptions, variable descriptions, validity tests, reliability tests, F tests, R2 tests, t tests, and Sobel Tests. The results of the study state that emotional intelligence has a positive effect on job satisfaction, compensation has a positive effect on job satisfaction, emotional intelligence has a positive effect on employee performance, compensation has no effect on employee performance, job satisfaction has a positive effect on employee performance, job satisfaction mediates the effect of emotional intelligence on employee performance, and job satisfaction mediates the effect of compensation on employee performance.